Youth Risky and Antisocial Behaviors in Newfoundland and Labrador: The Perspectives of Young People - Paul Alhassan Issahaku; Anda Adam; Alhassan Sulemana (Sage Open, 2024)
What do young people know about youth risky and antisocial behaviors (RASB) and what do they suggest could be done to address these behaviors? Although there is much literature on youth RASB, there has been little qualitative exploration of the question stated here. The current study aimed to broach the question and to fill the gap. The study contributes to extant literature by exploring types of RASB among youth, reasons for these behaviors, and possible ways to address them from the perspectives of young people in Newfoundland and Labrador (NL). Constructivist and interpretive perspectives where reality is determined through the social processes of subjectivity and intersubjectivity informed the study. Eighteen young people aged 15 to 24 years participated in three focus group discussions (FGD), and data were analyzed thematically. The three main themes resulting from the process were: (1) a spectrum of behaviors, which comprised six types of behaviors; (2) constructed explanations, where participants identified five possible reasons for RASB; and (3) suggested interventions, which comprised three subthemes on interventions to address youth RASB. The findings and their implications for further research and for policy and practice are discussed.